Transformative Rehabilitation: Exploring Prisoners' Experiences of the Community Based Health and First Aid Programme in Ireland - O'Sullivan, Róisín (European journal on criminal policy and research, 2020)
Using an assisted desistance framework, this paper explores the lived experiences of 11 volunteers on the Community Based Health and First Aid programme, which operates in 14 prisons across Ireland and aims to enhance community health, hygiene awareness and first aid knowledge among prisoners through peer-to-peer education. The findings suggest that participation fostered a sense of agency among volunteers and facilitated the development of a new non-criminal self, centred on the ‘wounded healer' identity. Additionally, participation appeared to deepen volunteers' pro-social bonds with other prisoners, staff and families. The contribution of these findings to knowledge about desistance and desistance-focused practice is considered.